Peranan Media Gambar dalam Meningkatan Keterampilan Membaca pada Siswa Kelas I - Zuliani, Rizky; Amalia, Dina; Syaikhah, Erina (Lembaga Yasin AlSys, 2023)
This study aims to improve students' reading skills by using media images in class I SD Negeri Karawaci 6. This type of research is classroom action research. The research subjects were grade I students. This classroom action research was conducted in two cycles with four components in each cycle, namely planning, action implementation, observation, and reflection. Data collection techniques were carried out using observation, interviews, documentation and field notes. The data analysis technique used is qualitative data analysis. Criteria for success seen from the process and product. The success of the process is measured based on improving the learning process in a better direction. The success of the product is measured based on the assessment of the final written test questions. The results of this study indicate that the use of flash card media can improve the reading skills of grade I students at SD Negeri Karawaci 6. Improvements can be seen in processes and products. Improving the quality of the process seen in student activities in learning. Improved quality of the process can be seen from the condition of students who are more confident in reading, more enthusiastic, and more independent. Process quality improvement has a positive impact on product quality improvement.